Enhancement of radionuclide bio-decontamination by screening highly efficient microalgae for Sr biomineralization. Issue 15 (6th July 2018) - Wang, Cong; Lee, Keon Ah; Choi, Eunpyo; Lee, Keun-Young; Lee, Seung-Yop; Jung, Kwang-Hwan; Park, Jungyul
Abstract : In this study, a new strategy for improving the radionuclide bio-decontamination (RBD) activity of microalgae by screening a better strain with high potential for biomineral production has been proposed. Abstract : In this study, a new strategy for improving the radionuclide bio-decontamination (RBD) activity of microalgae by screening a better strain with high potential for biomineral production has been proposed. A noninvasive dielectrophoresis (DEP)-based microalgae screening microplatform has been used to select the highly capable microalgae in RBD. Microalgae ( Chlorella vulgaris KMMCC9 ) with a high degree of competence in strontium (Sr) removal were successfully segregated against Chlorella vulgaris KCTC AG10002 that has relatively weak Sr removal activity under an AC electric field. C. vulgaris KMMCC9 with higher Sr biomineral competence (HSC) was also successfully segregated against others with lower Sr biomineral competence (LSC). Furthermore, after the screening and large-scale cultivation of C. vulgaris KMMCC9 with HSC, the microalgae showed highly effective Sr bio-decontamination in both non-radioactive and radioactive Sr contaminated water compared to wild-type (WT).